PENGARUH KEADILAN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PT. MUARA MALL TERNATE) - Albaar, Arsyila Humairah; Kamis, Ruslan (Jurnal Manajemen Sinergi, 2022)
This study aims to determine the effect of 1) To find outwhether organizational justice has an effect on employee turnoverintention at PT Muara Mall Ternate; (2) Knowing whetherorganizational justice has an effect on job satisfaction at PT Muara MallTernate; (3) Knowing whether job satisfaction has an effect onemployee turnover intention at PT Muara Mall Ternate; and (4)Knowing whether organizational justice has an effect on turnoverintention with job satisfaction as a mediating variable at PT Muara MallTernate. The number of research samples is 71 respondents. The dataanalysis technique used in this study is SEM analysis using SmartPartial Least Square (PLS) version 3 as a statistical test tool.Methodology: The analytical model used are Structural EquationModeling with SMART PLS as tools for the statistical test. Datacollection tools used are questionnaires and interviews, and thenumber of respondents was 71 employee.Finding: H1, H2, H3, and H4 are accepted at the 5% confidence level.n other words, the t-count value of each variable is greater than the ttableat the 5% confidence level.Conclusion: Te results of this study indicate that: (1) Organizationaljustice has a positive and positive effect on turnover intention at PT.Muara Mall Ternate; (2) organizational justice has a positive influenceon job satisfaction at PT. Muara Mall Ternate; (3) Job satisfaction has apositive influence on turnover intention at PT. Muara Mall Ternate; and(4) and job satisfaction is a variable capable of mediating the effect oforganizational justice on turnover intention at PT. Muara Mall Ternate